ETIKA KEPEMIMPINAN HINDU DALAM LONTAR WRATI SASANA (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2024)
The importance of applying high values in teaching Hinduism, because wanting to become a strong and disciplined generation is closely related to the spirit of a tenacious leader and understanding good knowledge of mind and body, natural knowledge and religious knowledge. This is not just a matter of the past in the current era of leadership. The emergence of leadership is seen as a more typical event. Competitiveness makes the process of achievement seem loose from theoretical order to moral violations. The consequence is that it produces an unprofessional image so that the leadership fails to carry out its duties properly. However, this actually causes suffering for the people led by it. This research is descriptive qualitative and linguistic analysis. The aim of this research is to produce high quality research and findings that can be scientifically proven through in-depth descriptions supported by primary and secondary data. This research collects data through observation, interviews and documents. Lontar Wrati Sasana is one of the much-discussed Lontar literatures which contains Hindu religious teachings about leadership ethics so that Hindus in particular understand and can apply Hindu religious teachings wisely and correctly. The ethical teachings of Hindu religious leadership contained in Lontar Wrati Sasana are upholding the ethics of yama brata, niyama brata, sad atatayi, avoiding killing or acts of Himsa and leaders must not be negligent.
Keywords: ethics; hindu leadership; wrati sasana